Implementing EITI at the Sub National Level : Emerging Experience and Operational Framework - Aguilar, Javier (World Bank, Washington, DC, 2014)
The fundamental rationale behind Extractive Industries Transparency Initiative (EITI) is that increased transparency and knowledge of revenues from the extractive industries will empower citizens and institutions to hold governments accountable. By implementing EITI at the sub national level, countries could reduce opportunities for mismanagement or diversion of funds from sustainable development purposes, especially for prominent oil, gas, or mining regions. It is also an effective way of strengthening EITI local ownership among stakeholders. This report presents a preliminary analysis of emerging experiences in EITI countries implementing sub national EITI. Six countries have been selected as case studies: Ghana, Indonesia, Mongolia, Nigeria, the Democratic Republic of the Congo (DRC), and Peru. Based on these experiences, the report proposes a common operational framework for implementing EITI at the sub national level, laying the ground for further practical guidelines on deepening or strengthening the sub national plans or activities of implementing countries.